Graduate School and a Life besides: Lessons Learned from My Undergraduate Days - Kendall L. Ferguson (University of North Florida, 2017)
This essay describes the expectations and demands placed on one returning student to graduate school who is faced with an array of competing roles. Her reflection on the ups and downs of undergraduate school experiences offers key lessons for persons about to embark on a similar education choice and the lifestyle challenges that it brings.